Manajemen Pengembangan Bakat dan Minat Siswa di MIN 15 Pidie Jaya - Zainal, Zainal; Alwi, Said; Fauzan, Fauzan (IAIN Manado, 2023)
Management of Student Talent and Interest Development at MIN 15 Pidie Jaya. The potential talents and interests students possess vary from one student to another. So that the gifted child's ability does not decrease, attention to the gifted child must be developed according to his talents and interests. Based on great expectations for talented children, it is necessary to manage the development of talents and interests. This study aims to determine the management of talent development and interests of students in MIN 15 Pidie Jaya and to find out the factors that influence the process of implementing talent and interest development in MIN 15 Pidie Jaya. This research uses qualitative research methods; the subjects of this study are the head, teachers, and students. Data collection techniques are carried out using interview, observation, and documentation techniques, and data analysis techniques are carried out by data reduction, data presentation, and conclusion drawing. The results showed that the process of developing students' talents and interests at MIN 15 Pidie Jaya went through four stages, namely the planning stage carried out at the beginning of the school year, the organizing stage by dividing tasks by the competencies possessed and forming an activity development team, the implementation stage is carried out by carrying out activities according to a predetermined schedule. The evaluation stage is carried out by observing the implementation of talent and interest development activities. The activities for developing students' talents and interests at MIN 15 Pidie Jaya are in the form of extracurricular activities which are carried out during class hours by the subject, and extracurricular activities that are carried out, namely first the fields of art in the form of dance, calligraphy, literacy of the Qur'an and MTQ, the two fields of sports in the form of table tennis, badminton, and football, the third field of discipline in the form of scouting activities. Several factors support and hinder the smooth implementation of the talent development program and student interests at MIN 15 Pidie Jaya, namely keeping factors including the amount of teacher willingness to carry out development activities and the support of parents for the implementation of development activities, the inhibiting factors are the lack of facilities and infrastructure and the absence of standard talent and interest development activity modules. Researchers hope related parties can compile an extracurricular activity module for Ibtidaiyah Madrasah students